Child growth monitoring and promotion practice and associated factors among health care workers at public health facilities in south Wollo Zone, Northeast Ethiopia: a facility-based cross-sectional study - Getabalew Getachew Kebede; Yeshimebet Ali Dawed; Kemal Ahmed Seid (BMC Nutrition, 2022)
Abstract Background Growth monitoring and promotion (GMP) is one of the health care priorities to assess and follow the growth pattern of children under 2 years old. Appropriate GMP services enable health care workers to control growth faltering early and child mortality. However, there is limited information showing the practice and associated factors of GMP service among health care workers in Ethiopia. Therefore, this study aimed to assess the practice and identify associated factors of GMP service among health care workers at public health facilities of the South Wollo Zone, northeast Ethiopia. Methods A facility-based cross-sectional study was conducted on 397 randomly selected health care workers in the South Wollo Zone, northeast Ethiopia, from May 25 to July 7, 2020. A pretested self-administered questionnaire and in-depth interview were used to collect the quantitative and qualitative data, respectively. Quantitative data were entered using Epi data Version 3.1 and exported to statistical software for social sciences (SPSS) version 20.0 software for further analysis. Binary logistic regression analyses were used to identify factors associated with GMP practice. Statistical tests at a P value < 0.05 with a 95% confidence interval were taken as a cutoff point to determine the statistical significance. Qualitative data were analyzed by using thematic analysis. Results In this study, the proportion of GMP practice among health care workers was 58.4% (95% CI: 54.0–63.0). Being a holder of first degree (AOR = 2.25; 95% CI: 1.01, 5.05), being a holder of a diploma (AOR = 3.52; 95% CI: 2.04, 6.09), work experience with GMP (AOR = 3.13; 95% CI: 1.58, 6.20), receiving GMP training (AOR = 4.83; 95% CI: 2.89, 8.06), availability of GMP equipment (AOR = 2.75; 95% CI: 1.64, 4.58) and having a positive attitude toward GMP (AOR = 3.70; 95% CI: 2.23, 6.17) were factors significantly associated with GMP practice. Conclusions and recommendations The proportion of GMP practice among health care workers was still low. Educational level, work experience with GMP, GMP training, GMP equipment and attitude toward GMP were positively associated with GMP practice. Availability of GMP equipment brings positive attitudes toward GMP, and GMP training for health care workers with less experience should be strengthened to improve GMP practice.